PELABELAN TOTAL SISI AJAIB SUPER (TSAS) PADA GABUNGAN GRAF ULAT BULU DAN BIPARTITE LENGKAP - Sudarsana, I Wayan; Fitria, Fitria; Musdalifah, Selvy (Univ. Tadulako, 2014)
An edge anti-magic total labelling, -EAMT, on graph with vertices and edges is bijektion , which has a set of edge weights with and . A super edge anti-magic total labelling , -SEAMT, if the vertex set of obtain the smallest labels . An -EAMT (SEAMT) labelling is called EMT (SEMT) labelling if and . Furthermore, is called the magic constant. A graph is said EMT, SEMT, -EAMT and -SEAMT if there is EMT, SEMT, -EAMT and -SEAMT labelling on graph , respectively. In this paper, we showed that the union of caterpillars and complete bipartite graph are SEAMT and SEMT, especialy for has (-SEAMT and -SEAMT with ; graph has -SEAMT and -SEAMT for ; and graph has -SEAMT and -SEAMT with where and for . Thus, graph is SEMT with for ; graph also SEMT with for ; as well graph is SEMT with for .